2011
DOI: 10.1007/s13402-011-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human pancreatic orthotopic tumor xenografts suitable for drug screening

Abstract: Background Efforts to identify novel therapeutic options for human pancreatic ductal adenocarcinoma (PDAC) have failed to result in a clear improvement in patient survival to date. Pancreatic cancer requires efficient therapies that must be designed and assayed in preclinical models with improved predictor ability. Among the available preclinical models, the orthotopic approach fits with this expectation, but its use is still occasional. Methods An in vivo platform of 11 orthotopic tumor xenografts has been ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…16 Patient-derived tumorgrafts have been previously demonstrated to recapitulate the altered pathways of the primary tumor from which they were derived. 17,18 In order to demonstrate similar pathway stability in our cohort and to ensure that any expression differences were not responsible for differences in engraftment, IHC was performed and the correlation between samples was determined. There was excellent inter-rater agreement (K = 0.81–1.00) for IHC scoring between each primary tumor and paired tumorgraft for every marker tested, thus demonstrating expression stability (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…16 Patient-derived tumorgrafts have been previously demonstrated to recapitulate the altered pathways of the primary tumor from which they were derived. 17,18 In order to demonstrate similar pathway stability in our cohort and to ensure that any expression differences were not responsible for differences in engraftment, IHC was performed and the correlation between samples was determined. There was excellent inter-rater agreement (K = 0.81–1.00) for IHC scoring between each primary tumor and paired tumorgraft for every marker tested, thus demonstrating expression stability (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The engraftment efficiency was about 61% (14), a higher efficiency rate than that we report here for the establishment of primary PDAC cell cultures. However, several studies demonstrated that subcutaneously xenograft models often do not recapitulate the essential features of tumor growth, native tumor microenvironment, and locally invasive and metastatic disease (31), supporting the development of orthotopically implanted tumors as a critical preclinical tool for testing new agents. Another crucial step for the development of the PDAC mouse models consisted of the application of BLI, a low-cost longitudinal in vivo imaging method (32).…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase-expressing cells CP15-Luc were established by transducing the parental cells CP15 cell line established from CP15 tumors [33, 34] with a recombinant retrovirus pLHCluc following standard procedures and selected in 0.2 mg/ml hygromycin. Human pancreatic ductal epithelial cells (HPDE) were kindly provided by Dr. FX Real (CNIO, Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%